Raman Profile Assessments of Qualifying Variably Graphitized Carbon Materials for Exclusive Industrial Applications - Anant Babu Marahatta (Advances in Materials Science and Engineering)
In material science and engineering, the carbons and carbon research works are the most triggering subjects of interest owing to their promising applicative aptitudes and functionalizing domains apparent mainly to the internal graphitic heterogeneity, percentage crystallinity (%C), and degree of graphitization (DOG); C-configurations and graphene layouts; structural deformations and crystallographic defects; and crystallite sizes (La) and growths. More importantly, the progressive changes in their internal phase transitions and transformations plus the dissimilar proportions of microstructural modifications and improvisations at various critical stages upon increasing subsequent metamorphoses and graphitization add more momentum to their day-to-day attention. In this contribution, the author assesses the same functionalizing assets existing differently in the dissimilarly carbonized and/or graphitized Toray industries manufactured carbon materials: activated carbon (AC) (MSC-30, T = ∼700°C) and four types of carbon blacks (CBs) (CB1 (Toyotanso), T = ∼800°C, CB2 (EC-300J); T = ∼1400°C, CB3 (DENKA); T = ∼2000°C, CB4 (TB-3845); T > 2500°C) through the genuine Raman spectroscopy means, and reports their applicative qualifications explicitly. Among the samples, the low temperature amorphous AC material is found to exhibit the poorest microstructural graphitic domains and therewith dependent applicative features compared to CBs and is found to possess contrasting configurations of the basic structural units (BSUs) to those of the latter and semigraphite and graphite. Within the members of the CBs, the disparate alignments of the BSUs and the predominant variations in the resulting functional domains are noticed. The in-depth analyses of the intensity ratio ID/IG of each of their D- and G-bands not only speculate their variable %C, %DOG, and defects quantity but also depict their contrasting morphological textures and basal plane and edge plane ratios. Tuinstra–Koenig formula computed crystallite size Laand growths justify the superior functional qualifications of the CB4 (La = 9.2 nm) over the others along with verifying its weakly cross-linked, compactly aligned yet highly parallel crystallite phase matrices. The author believes that this article presents a thorough Raman profile assessing schemes indispensable to probe the generic qualifications of a wide range of carbon materials efficacious in diverse industrial areas.